2001
DOI: 10.1111/1469-8986.3830399
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic inhibition among schizotypal personality disorder subjects

Abstract: Schizotypal personality disorder (SPD) is theoretically part of the schizophrenia spectrum both clinically and neurobiologically. A liability for developing schizophrenia may be associated with dysfunction of dorsolateral prefrontal cortex (DLPFC) and its cortical and/or subcortical circuitry. If so, abnormalities on tasks associated with DLPFC functioning among SPD subjects would support the thesis that SPD is neurobiologically related to schizophrenia. Antisaccade and ocular motor delayed response performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Interestingly, however, latency (Brenner et al, 2001;Ettinger et al, 2005b;Gooding, 1999;O'Driscoll et al, 1998) and spatial accuracy (Brenner et al, 2001;Ettinger et al, 2005b) appear unaffected amongst schizotypal individuals, suggesting that these two high-risk groups display only partially overlapping genetic vulnerabilities, at least with regards to antisaccade function.…”
Section: Do Antisaccade Deficits Mark Genetic Liability For Schizophrmentioning
confidence: 99%
“…Interestingly, however, latency (Brenner et al, 2001;Ettinger et al, 2005b;Gooding, 1999;O'Driscoll et al, 1998) and spatial accuracy (Brenner et al, 2001;Ettinger et al, 2005b) appear unaffected amongst schizotypal individuals, suggesting that these two high-risk groups display only partially overlapping genetic vulnerabilities, at least with regards to antisaccade function.…”
Section: Do Antisaccade Deficits Mark Genetic Liability For Schizophrmentioning
confidence: 99%
“…Wonodi et al, 2006) have recruited schizotypal individuals using advertisements and following up with clinical interviews in order to yield a group of individuals meeting diagnostic criteria for schizotypal personality disorder. Others (Brenner et al, 2001) have studied patients diagnosed with schizotypal personality disorder or individuals presenting with subsyndromal or prodromal symptoms of psychosis (e.g. Nieman et al 2007).…”
Section: Schizophrenics’ Performance On Scanpaths and Visual Search Tmentioning
confidence: 99%
“…Brenner et al (2001) reported that patients diagnosed with DSM-IV schizotypal personality disorder displayed normal saccadic performance on both antisaccade and memory-guided tasks, though there was some evidence of inhibitory deviance in a subgroup of SPD subjects. It is possible that the overall negative findings in the Brenner et al (2001) investigation are attributable to the less demanding nature of the antisaccade task that was used.…”
Section: Schizophrenics’ Performance On Scanpaths and Visual Search Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of deficits in visual perceptual and oculomotor functions in the schizophrenia spectrum have been mixed (Braff, 1981;Brenner, McDowell, Cadenhead, & Clementz, 2001;Cadenhead, Light, Geyer, McDowell, & Braff, 2002;Larrison, Ferrante, Briand, & Sereno, 2000;Siever, Coursey, Alterman, Buchsbaum, & Murphy, 1984;Siever, Friedman, et al, 1993;Siever, Kalus, & Keefe, 1993;Siever et al, 1990). Silverstein, Raulin, Pristach, and Pomerantz (1992) employed a psychosis-vulnerability scale and reported normal performance on tests of perceptual organisation.…”
Section: Introductionmentioning
confidence: 99%